2016
DOI: 10.1007/s10943-016-0295-7
|View full text |Cite
|
Sign up to set email alerts
|

Ministry-Related Burnout and Stress Coping Mechanisms Among Assemblies of God-Ordained Clergy in Minnesota

Abstract: Clergy members suffering from burnout face both personal and professional complications. This study assessed occupational burnout and stress coping mechanisms among ministers affiliated with the Assemblies of God, a denomination that has received little attention in previous burnout-related studies. A cross-sectional design was employed using two instruments with acceptable psychometric properties. Approximately 65 % of those surveyed were either suffering from burnout or on the verge of burnout. Statistical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…As a coping strategy, venting is considered passive, or ineffective at managing stress and may, in fact, intensify one’s stress level [ 56 ]. Visker, Rider and Humphers-Ginther [ 57 ] acknowledged that it was generally acceptable to discuss personal feelings about stress, and excessive voicing of displeasure (venting) should be discouraged. However, venting one’s frustrations is often associated with a cathartic relief of stress symptoms [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a coping strategy, venting is considered passive, or ineffective at managing stress and may, in fact, intensify one’s stress level [ 56 ]. Visker, Rider and Humphers-Ginther [ 57 ] acknowledged that it was generally acceptable to discuss personal feelings about stress, and excessive voicing of displeasure (venting) should be discouraged. However, venting one’s frustrations is often associated with a cathartic relief of stress symptoms [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reducing occupational distress is important for religious entities, including numerous Christian denominations, because of the correlation of multiple types of clergy stressors with burnout (Adams, Hough, Proeschold-Bell, Yao, & Kolkin, 2017; Francis, Village, Robbins, & Wulff, 2011; Visker, Rider, & Humphers-Ginther, 2017). The level of depressive symptoms of the clergy in this sample was higher than that observed in the general population (Proeschold-Bell et al, 2013), demonstrating a need to assess and respond to depressive symptoms in clergy.…”
Section: Discussionmentioning
confidence: 99%
“…Burnout can be conceptualized as high levels of emotional exhaustion, high levels of depersonalization, and low levels of personal achievement (Maslach & Jackson, 1981). In a study among Assembly of God church leaders, 65% reported suffering from or bordering on burnout (Visker et al, 2017). In a sample of parish-based United Methodist clergy, 19% reported high emotional exhaustion, 10% high depersonalization, and 11% low personal accomplishment (Doolittle, 2007).…”
Section: Ministry Stress and Well-beingmentioning
confidence: 99%